The Problem of Muslims' Identity in Western Europe - L. R. Sadykova (Международная аналитика)
The paper is devoted to a topical subject of current political discussions, namely, the identity of Muslims living in the countries ofthe European Union (EU). Development ofinformation technologies significantly affects almost all spheres of life of every state and citizens living there. To benefit from new possibilities, an individual, as well as a religious community or civilization group should adapt their peculiarities and identities to the society of different moral and cultural values. Nowadays Western Europe is concerned about a complex of such tasks.. In spite of the fact that such countries as Great Britain, France and Germany are among the most stable on the planet, both in political and economic terms, the problems of identity disturb modern Europeans. These problems are further aggravated because of the ongoing flow of migrants, mostly Мuslims, who yearn to keep their originality and, especially, religious identity.